Pengaruh Citra Merek, Kualitas Produk, Dan Harga Terhadap Keputusan Pembelian Pada Produk Brand Eiger (Studi Kasus Mahasiswa Fakultas Ekonomi dan Bisnis Universitas Islam Malang Angkatan 2020) - Khoirullah, Ahmad; Basalamah, Muhammad Ridwan; Wahono, Budi (UNIVERSITAS ISLAM MALANG, 2023)
Abstract This study aims to examine and explain the influence of brand image, product quality and price on purchasing decisions for brand Eiger products (Case Study of Economics and Business Students of the Islamic Faculty of Malang Class of 2020). This research includes a type of research with quantitative. The method used is multiple linear regression. The sampling technique uses the formula from Solvin with the calculation results of 88 samples. To solve the problem in this study using SPSS with the help of validity test, reliability test, normality test, multiple linear regression analysis, multicollinearity test, heteroscedasticity test, F test, and t test. The results showed that simultaneously. Variables Brand Image (X1), Product Quality (X2), Price (X3) have a significant effect simultaneously on Purchase Decision (Y). And there is a partial influence between Brand Image (X1), Product Quality (X2), Price (X3) on Purchase Decision (Y). Keywords: Brand Image, Product Quality, Price, Purchase Decision